Pulmonary microlithiasis – A case report. (2016) - Mahmood, Khalid; Ubaid, Muhammad; Mahmood, Aamer
Abstract: Pulmonary alveolar microlithiasis is a rare diffuse lung disease characterized by widespread sand-like intra-alveolar calcifications (calcospherites composed of calcium and phosphorus). Around 800 cases have been reported in the literature to date. We report here a case of a 35 years old female with prolonged h/o of exertional dyspnoea and mild cough. Clinical examination was mostly normal. Her Chest X-Ray revealed bilateral multiple nodular opacities (sand storm appearance). CT Scan chest showed diffuse micronodular calcifications with septal thickening, compatible with alveolar microlithiasis. Pulmonary function tests showed moderately restrictive lung disease. Bronchoscopic alveolar lavage revealed calcospherites in the alveloli and bronchi confirming the diagnosis of pulmonary alveolar microlithiasis.